1984
DOI: 10.1107/s0108768184002378
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental studies of the charge density in urea

Abstract: X-ray structure amplitudes [F~o[ for urea at 123 K have been derived experimentally for 318 reflections, IF[ > 3tr(Fo), sin 0/h < 1.15 ,~-~. Corresponding amplitudes [F'ol have also been calculated for a simulated crystal structure with the charge density derived from a 6-31G** wavefunction for the isolated urea molecule. The nuclear positional and anisotropic thermal parameters at 123 K were those obtained by neutron diffraction. The [F~[ were placed on an 'absolute' scale with the [F'ol. Simple pseudoatom mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 5 publications
4
50
0
Order By: Relevance
“…Crystal used for neutron diffraction study had forms {110} and {001}; crystal 0-8x0-8xl.8mm, measured with a microscope, volume 1.15 mm 3 in agreement with volume (1.17 mm 3) calculated from crystal weight (1-55 mg) and density (1.330gem -3) measured by flotation in benzene/bromoform. Neutron data collected at Brookhaven High Flux Beam Reactor, (Swaminathan, Craven, Spackman & Stewart, 1984) are a = 5.578 (1), c = 4.686 (I)A,. These agree with the X-ray values of Mullen & Hellner (1978), a = 5.576 (3), c =4-686 (3),~.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal used for neutron diffraction study had forms {110} and {001}; crystal 0-8x0-8xl.8mm, measured with a microscope, volume 1.15 mm 3 in agreement with volume (1.17 mm 3) calculated from crystal weight (1-55 mg) and density (1.330gem -3) measured by flotation in benzene/bromoform. Neutron data collected at Brookhaven High Flux Beam Reactor, (Swaminathan, Craven, Spackman & Stewart, 1984) are a = 5.578 (1), c = 4.686 (I)A,. These agree with the X-ray values of Mullen & Hellner (1978), a = 5.576 (3), c =4-686 (3),~.…”
Section: Methodsmentioning
confidence: 99%
“…The present neutron diffraction studies were undertaken when large discrepancies were found between the anisotropic thermal parameters at 123 K reported by Guth et al (1980) and the corresponding values obtained from an X-ray analysis at the same temperature (Swaminathan, Craven, Spackman & Stewart, 1984). It seemed desirable to investigate these discrepancies as part of a detailed extensive study of the molecular structure and thermal motion of urea over a range of temperature.…”
Section: Introductionmentioning
confidence: 98%
“…version of an earlier code (STRUFAC) used in several previous analyses of model X-ray data generated from theory (see, for example, Spackman, 1979;Swaminathan, Craven, Spackman & Stewart, 1984;Ritchie, Cromer, Stewart, Wasserman & Ryan, 1985;Chandler & Phillips, 1986;Chandler, Figgis, Reynolds & Wolff, 1994). It incorporates an analytical Fourier transformation of Gaussian orbital products (Chandler & Spackman, 1978) and the option to include anisotropic thermal motion parameters for each atom.…”
Section: Compute Molecular Propertiesmentioning
confidence: 99%
“…These features were of interest to us because of recent studies of the charge-density distribution in related crystal structures, including parabanic acid at 298 K (Craven & McMullan, 1979) and at 123 K (He, Swaminathan, Craven & McMullan, 1986), urea (Swaminathan, Craven, Spackman & Stewart, 1984) and thiourea (Mullen, Heger & Treutmann, 1978;Mullen, 1982;Kutoglu, Scheringer, Meyer & Schweig, 1982). We have redetermined the crystal structure of TUPA with greater accuracy using X-ray (Mo Ka)…”
Section: Introductionmentioning
confidence: 99%